Valence, spin, and orbital state of Co ions in one-dimensional Ca 3Co 2O 6: an x-ray absorption and magnetic circular dichroism study - Burnus, Tobias; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2006)
We have investigated the valence, spin, and orbital state of the Co ions in the one-dimensional cobaltate Ca3Co2O6 using x-ray absorption and x-ray magnetic circular dichroism at the Co−L2,3 edges. The Co ions at both the octahedral Cooct and trigonal Cotrig sites are found to be in a 3+ state. From the analysis of the dichroism we established a low-spin state for the Cooct and a high-spin state with an anomalously large orbital moment of 1.7μB at the Co3+trig ions. This large orbital moment along the c-axis chain and the unusually large magnetocrystalline anisotropy can be traced back to the double occupancy of the d2 orbital in trigonal crystal field.